High-resolution decadal-scale eruption age dating of young oceanic basalts at an active hydrothermal vent site - Sims, Kenneth W. W.; Kant, Lisa B.; Stark, Gregory J.; Reagan, Mark K.; Standish, Jeff J.; Langmuir, Charles H. (Frontiers in Geochemistry, 2024)
210 Pb/ 226 Ra), ( 226 Ra/ 230 Th), ( 230 Th/ 238 U) and ( 234 U/ 238 U) disequilibria for eleven lavas from the ABE vent site in the Lau Basin. Most ABE lavas have ( 210 Pb/ 226 Ra) > 1 and ( 226 Ra/ 230 Th) > 3. These results indicate that most of these lavas erupted within the past 100 years. Model ages calculated assuming initial ( 210 Pb/ 226 Pb) = 1.8-2.0 further constrain the timing of eruption, suggesting that more than half of the lavas erupted within the past 60 years. When combined with complementary data (side-scan sonar, lava flow morphology, tectonic mapping), this high-resolution record provides fundamental time constraints for interdisciplinary studies examining oceanic crustal construction and development of the hydrothermal system in the ABE vent field. Notably the youngest samples cluster around the active vent sites indicating that the ABE vent site's location is a direct consequence of this concentrated young volcanism. This study is the first high resolution U-series study of a seafloor vent site and demonstrates the potential of using ( 210 Pb/ 226 Ra) for the determination of lava ages for young submarine lavas in spreading environments with active hydrothermal venting. As such these ( 210 Pb/ 226 Ra) measurements hold the promise for addressing in far greater detail the connections between spreading ridge eruptive and hydrothermal activity on the decadal to century time scales.